This is how it always is eaudiobook A novel. - Frankel, Laurie (Macmillan Audio, 2017)
The Reese Witherspoon x Hello Sunshine Book Club Pick *Named one of the top 10 books of 2017 by People Magazine * "It made me laugh, it made me cry, it made me think." —Liane Moriarty, #1 New York Times bestselling author of Big Little Lies This is how a family keeps a secret...and how that secret ends up keeping them. This is how a family lives happily ever after...until happily ever after becomes complicated. This is how children change...and then change the world. This is Claude. He's five years old, the youngest of five brothers, and loves peanut butter sandwiches. He also loves wearing a dress, and dreams of being a princess. When he grows up, Claude says, he wants to be a girl. Rosie and Penn want Claude to be whoever Claude wants to be. They're just not sure they're ready to share that with the world. Soon the entire family is keeping Claude's secret. Until one day it explodes. Laurie Frankel's This Is How It Always Is is a novel about revelations, transformations, fairy tales, and family. And it's about the ways this is how it always is: Change is always hard and miraculous and hard again, parenting is always a leap into the unknown with crossed fingers and full hearts, children grow but not always according to plan. And families with secrets don't get to keep them forever. "The audiobook will undoubtedly steal hearts" - AudioFile